A cloud based knowledge discovery framework, for medicinal plants from PubMed literature. (2019) - Niyati Kumari, Behera; Mahalakshmi, G.S.
Abstract: MOBILE healthcare systems focus to achieve two specific goals: Making e-health applications and medical information available anywhere and anytime, and the invisibility of computing details. In this paper a cloud based mobile application has been initiated to identify herbal medicines of interest to the general population. This system responds to queries posted by users on medicinal plants relating to a particular disease by analysing research articles from PubMed via PubMed CLOUD and MeSH thesaurus. In this proposal, we particularly focus on applying text mining techniques to the biomedical literature, to unearth information concerning the curing of disease based upon the phyto-chemical properties of medicinal plants. The framework also includes an ontological structure to buffer the retrieved information, and thereby enhances the overall system efficiency.